Developing EFL Teachers’ Skills in Creating Digital Photo Story Videos as Learning Media - Weningtyas Parama Iswari; Noor Rachmawaty; Effendi Limbong (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2023)
Along with the increase in the use of digital materials, teachers need to possess skills in creating these materials. Digital photo story videos are among the alternatives to digital materials that are easy to create. However, some teachers still had limited technological skills. A workshop was conducted online for three months from August to November 2020. This workshop trained some participants in creating digital photo story videos as learning media. The participants consisted of twelve secondary school teachers of English from different districts in East Kalimantan.  Data were gathered from discussions, reflections and outcomes of the workshop. The results revealed some indicators of teachers’ development, not only in teachers’ technological skills but also in some other domains. The participants gained new knowledge regarding simple technology for creating videos, and their understanding of the TPACK framework was also detected. They were able to operate the software applications introduced, and created the digital story videos successfully, despite a few technical problems.  In addition, they showed their initiative to explore new applications to upgrade their videos, and intention to learn more about video editing. Effectively, their attitude towards the workshop and their videos was positive, and socially, they confirmed that their networking expanded as they met and worked together with colleagues from different districts. This study has added the existing evidence that teachers should enhance their technological skills to keep up with the rapidly changing world. Future researchers are advised to see the after-workshop effects of such a workshop on its participants’ teaching practice and professional development.